Association between obesity and neurodevelopmental delay risk in children under five years: A study from Tumbes, Peru - Miriam Arredondo-Nontol; Rodolfo Arredondo-Nontol; Narcisa Reto; Alexis Germán Murillo Carrasco (PLoS ONE, 2026)
Background Childhood obesity is an emerging public health concern in low- and middle-income countries and may be associated with early neurodevelopmental vulnerability. Evidence on this association during early childhood remains limited, particularly in Latin American settings. Objective To evaluate the association between childhood obesity and neurodevelopmental delay risk in children under five years of age attending public healthcare facilities in Tumbes, Peru, and to develop a multivariable nomogram for probabilistic risk estimation. Methods An analytical cross-sectional study was conducted between 2022 and 2024 among children aged 0–59 months receiving care at two EsSalud healthcare facilities in Tumbes. Neurodevelopment was assessed using the Evaluación del Desarrollo Infantil (EDI), classifying children as having normal development, developmental lag, or being at risk of developmental delay. Childhood obesity was defined using WHO weight-for-height standards. Sociodemographic, clinical, and behavioral variables were collected. Associations were evaluated using proportional odds ordinal logistic regression guided by a directed acyclic graph. A nomogram was developed based on the final model and internally validated using bootstrap resampling (1,000 iterations). Results The final analytical sample included 431 children; 27% were classified as obese and 19% had anemia. According to the EDI, 58% had normal development, 36% developmental lag, and 6% were at risk of developmental delay. Childhood obesity was independently associated with higher cumulative odds of neurodevelopmental delay risk (OR = 2.73; 95% CI: 1.66–4.51). Male sex and older age group were also associated with increased risk, while higher caregiver knowledge of complementary feeding showed a protective association. Physical activity compliance and anemia were not independently associated in the multivariable model. The nomogram demonstrated acceptable internal discrimination (AUC > 0.7). Conclusions Childhood obesity was associated with increased neurodevelopmental delay risk in children under five years of age. An explanation-informed nomogram using routinely available variables may support early risk stratification in primary care, although external validation is required before broader implementation.